Effect of interruption in sedentary behavior on glycemic control in gestational diabetes - Trujillo Gittermann, Luz María.; Gutiérrez Pinto, Jorge.; Oetinger Giacoman, Astrid von. (Peruvian Society of Obstetrics and Gynecology, 2023)
Physical activity produces beneficial effects in pregnant women. In spite of this, most of them present high levels of sedentary behavior. The objective of the study was to demonstrate the effect of a break in sedentary behavior on metabolic control in a 36-year-old patient with gestational diabetes. The intervention consisted of reorganizing her daily routine and performing a sedentary behavior break protocol. The patient achieved optimal metabolic control after the beginning of the intervention and until the end of pregnancy. The sedentary behavior break protocol added to the reorganization of the patient's routine proved to be effective in achieving glycemic control and avoiding complications associated with gestational diabetes.
Efecto de la interrupción en la conducta sedentaria sobre el control glicémico en la diabetes gestacional
Keywords: Embarazo; Diabetes gestacional; Conducta sedentaria; Ejercicio físico